FILSAFAT PANCASILA DAN FILSAFAT HUKUM SEBAGAI DASAR RULE OF MORAL - Luh Suryatni (JURNAL ILMIAH HUKUM DIRGANTARA, 2016)
Pancasila as the philosophy of life of the Indonesian nation, grow and develop along with the growth and development of the Indonesian nation. The principles contained in Pancasila rooted in the culture and experience of the Indonesian nation, which developed as a result of the nation's efforts in seeking answers to the essential issues concerning the meaning on the nature of things and become a part of Indonesian life. Philosophy of Law adopted will serve as the foundation of philosophical and norms of criticism for the entry into force of the Law and the Rules of the overall processes of the legal life of the community in question, which includes the creation and implementation and enforcement. Philosophy of Law were adopted it was part of the worldview espoused in the communities concerned. It can be said that the Philosophy of Law is the adoption of a view of life in the field of rule of law is derived from rule of morals. Keyword: Pancasila phylosophy, Phylosophy of law, and Rule of morals.